A review of the genus Epitrichius Tagawa, with an analysis of the internal sacarmature of the male genitalia (Coleoptera: Scarabaeidae: Cetoniinae) - Lis, Chun-Lin; Yang, Ping-Shih; Hsu, Kuo-Sheng; Wang, Chuan-Chan (Zootaxa, 2008)
This paper redefines the Oriental genus Epitrichius Tagawa (Coleoptera: Scarabaeidae: Cetoniinae: Trichiini) and gives descriptions and illustrations of Epitrichius shinshuingensis, a new species from Taiwan. The genus also includes other six species: E. bowringii (Thomson) new combination, E. cupreipes (Bourgoin) new combination, E. elegans (Kano), E. fraterculus (Moser) new combination & new status, E. lagopus (Fairmaire), and E. versutus (Krikken) new combination. The following species names are placed in synonymy with E. bowringii: Trichius bifasciatus (Moser) new synonym and T. miyashitai (Krajcik) new synonym. In addition, E. fraterculus duporti (Bourgoin) is placed in synonymy with E. fraterculus. Information on the specimen examination, distribution and known biology of all species is provided. A key to the species of the genus is included. The sclerotized armatures of the internal sac of the male genitalia of Epitrichius was examined and found to provide strong support to separate this genus from other Trichiini genera. This set of characters was also found to be reliable in identifying species in groups with variable parameres.